The causal nexus of consumer and business confidence indexes in early pandemic period: Evidence from OECD countries - Inna Bielova; Jaroslav Halík; Lyudmila Ryabushka (Journal of Risk and Financial Management, 2021)
The COVID-19 pandemic has been shown dire consequences for the global economy, not only in the past and present but also in the future. These consequences are not only humanitarian but also financial and economic. This article raises the question of whether the state of the health system is a factor that determines the direction of changes in consumer and business sentiment during the COVID-19 or whether other factors are more significant. The goal is to find out whether there is real progress in the national health system of a particular country or a regression and on this base to answer the question: What is more important for the expectations of the population and industry during the spread of the pandemic; the dynamics of the development of the health system or other factors? To assess the dynamics of the development of the health care system in different countries, we used the annual data on individual health indicators of the OECD countries for 2006-2019. There were identified countries with dynamic development and a slowing/deteriorating health system. Based on Granger's approach in EViews, we used the Augmented Dickey-Fuller test and admit that health care systems are not a determining factor in consumer and business sentiment during a pandemic, i.e., only economic factors. The research contributes to the developed COVID-19 research by examining the impact of the changes in the mutual influence of Confidence indexes and macro indicators during the pandemic.
Keywords: 330; business confidence index; consumer confidence index; COVID-19; Granger causality test; panel data; taxonomic development coefficient